Intervening in Anti-Immigrant Sentiments: The Causal Effects of Factual Information on Attitudes toward Immigration. Issue 1 (September 2021) - Abascal, Maria; Huang, Tiffany J.; Tran, Van C.
If preferences on immigration policy respond to facts, widespread misinformation poses an obstacle to consensus. Does factual information about immigration indeed affect policy preferences? Are beliefs about immigration's societal impact the mechanism through which factual information affects support for increased immigration? To address these questions, we conducted an original survey experiment, in which we presented a nationally representative sample of 2, 049 Americans living in the United States with facts about immigrants' English acquisition and immigrants' impact on crime, jobs, and taxes—four domains with common misperceptions. Three of these factual domains (immigration's impact on crime, jobs, and taxes) raise overall support for increased immigration. These facts also affect beliefs that are directly relevant to that information. Moreover, those beliefs mediate the effect of factual information on support for increased immigration. By contrast, information about English acquisition affects neither policy preferences nor beliefs about immigration's impact. Facts can leverage social cognitions to change policy preferences.